Single-stage repair of secondary unilateral cleft lip-nose deformity in adults. Issue 1 (January 2020) - Zhou, Fan; Lin, Wen; Du, Yifei; Li, Sheng; Jiang, Hongbing; Wan, Linzhong; Yuan, Hua
Abstract: Correction of cleft lip-nose deformity in adult patients is different from that in children. One-stage correction has proved to be a suitable technique for patients with cleft-lip nose deformity. This study aimed to explore a particular single-stage method and evaluate the effect of simultaneous reparation of secondary unilateral cleft lip-nose deformities. Cleft lip patients who had previously undergone nasolabial surgery with residual poor nasal/lip appearance were included. The alveolar bone defect was repaired with granular costal cortical bone. Lip revision and rhinoplasty were performed using diced costal cartilage. The lip, nose, and alveolar deformities were corrected in one stage. From 2011 to 2017, 53 cases were treated. The vermilion discrepancy was corrected in all cases. Fifty-one patients were successfully treated, with primary healing in the bony recipient area. Cancellous bone exposure occurred in two cases. The wounds were healed after debridement and drainage. Appearances were improved in all patients. The mean change in columella–labial angle ranged from 82.50 to 92.78° ( p  < 0.001). This one-stage correction appears to have led to a distinct improvement in the nasal tip projection and lip. The method is considered to be effective and reliable in patients with secondary unilateral cleft lip-nose deformities.